Synthesis, thermo-physical properties and convection heat transfer of carbon based hybrid nanofluids / Houman Yarmand - Houman , Yarmand (2016)
Water, engine oil and ethylene glycol are commonly used as working fluids for transfer of heat in many industrial equipment such as heat exchangers, cooling devices and solar collectors. Little improvement in efficiency of heat exchanging equipment could lead to huge savings in initial and operational costs. One way to achieve this aim is to enhance the effective thermal conductivity of fluids that transfer the heat. Since the thermal conductivity of most of the heat exchanging liquids is low, there has been interest to use suspended solid particles to enhance the thermal conductivity of the base-fluid. Dispersion of micrometer or even millimeter particles in base-fluid was attempted earlier by researchers. However, these earlier attempts had faced obstacles such as, increase in pressure drop, sedimentation of particles and erosion of equipment. Choi and his co-worker in 1995 had found a new class of fluids with suspension of nanoparticles that is called “nanofluid”. Investigation supports that the nanoparticles have the ability to improve the effective thermal conductivity of base fluid and are useful for different industrial applications. In the present study, a facile method is used for synthesis of functionalized graphene nanoplatelets (f-GNP) nanofluids and hybrid carbon based nanofluids. The effective thermal conductivity, density, viscosity, specific heat capacity, heat transfer coefficient and friction factor for fully developed turbulent flow of functionalized GNP/water and hybrid nanofluids flowing through a square pipe at a constant heat flux were studied. The surface characterization was performed by various techniques such as XRD, FESEM, FTIR and Raman. All the nanofluids were prepared by dispersing the functionalized nanoparticles in base fluid (water) without adding the surfactants. The synthesized nanofluids were stable for a long time and no sedimentation was observed. The experimental data for all the prepared nanofluids have shown significant enhancement in thermal conductivity and heat transfer coefficient in comparison to the corresponding base fluid the water data. In this investigation, some improved empirical correlations were proposed based on the experimental data for evaluation of the Nusselt number and friction factor.